'Friends and Neighbors' Voting Under Mixed-Member Majoritarian Electoral Systems: Evidence from Lithuania. Issue 1 (2nd January 2019) - Herron, Erik S.; Lynch, Michael S.
ABSTRACT: The concept of 'friends and neighbors' voting, in which voters are more likely to support locally-affiliated candidates, has a long tradition in the study of elections and representation. The concept was established in the study of American politics and has been tested in other political and social environments. The focus of 'friends and neighbors' voting has been on single and multi-seat constituency-based elections. This emphasis leaves open an important question: Does the concept carry over to party-list elections? This article takes advantage of the features of Lithuania's mixed-member electoral system to assess how 'friends and neighbors' voting may influence constituency and party-list races. We find that the magnitude of effect for 'localness' is greater when candidates dual-list in constituencies and on party lists. However, residency has a significant effect on voting outcomes even for candidates contesting only on the party list and for those in hopeless list positions, suggesting that 'friends and neighbors' voting may extend even to electoral systems that are not constituency-based.